Robotic-assisted unicompartmental knee arthroplasty has a greater early functional outcome when compared to manual total knee arthroplasty for isolated medial compartment arthritis. Issue 1 (January 2020) - Clement, Nicholas D.; Bell, Allison; Simpson, Philip; Macpherson, Gavin; Patton, James T.; Hamilton, David F.
Abstract : Aims: The primary aim of the study was to compare the knee-specific functional outcome of robotic unicompartmental knee arthroplasty (rUKA) with manual total knee arthroplasty (mTKA) for the management of isolated medial compartment osteoarthritis. Secondary aims were to compare length of hospital stay, general health improvement, and satisfaction between rUKA and mTKA. Methods: A powered (1:3 ratio) cohort study was performed. A total of 30 patients undergoing rUKA were propensity score matched to 90 patients undergoing mTKA for isolated medial compartment arthritis. Patients were matched for age, sex, body mass index (BMI), and preoperative function. The Oxford Knee Score (OKS) and EuroQol five-dimension questionnaire (EQ-5D) were collected preoperatively and six months postoperatively. The Forgotten Joint Score (FJS) and patient satisfaction were collected six months postoperatively. Length of hospital stay was also recorded. Results: There were no significant differences in the preoperative demographics (p ⩾ 0.150) or function (p ⩾ 0.230) between the groups. The six-month OKS was significantly greater in the rUKA group when compared with the mTKA group (difference 7.7, p < 0.001). There was also a greater six-month postoperative EQ-5D (difference 0.148, p = 0.002) and FJS (difference 24.2, p < 0.001) for the rUKA when compared to the mTKA. No patient was dissatisfied in the rUKA group and five (6%) were dissatisfied in the mTKA, but this was not significant (p = 0.210). Length of stay was significantly (p < 0.001) shorter in the rUKA group (median two days, interquartile range (IQR) 1 to 3) compared to the mTKA (median four days, IQR 3 to 5). Conclusion: Patients with isolated medial compartment arthritis had a greater knee-specific functional outcome and generic health with a shorter length of hospital stay after rUKA when compared to mTKA. Cite this article: Bone Joint Res 2019;9(1):15–22.